Explaining regional disparities in housing prices across German districts - Lars Brausewetter; Stephan L. Thomsen; Johannes Trunzer (Halle Institute for Economic Research (IWH), 2022)
Over the last decade, German housing prices have increased unprecedentedly. Drawing on quality-adjusted housing price data at the district level, we document large and increasing regional disparities: Growth rates were higher in 1) the largest seven cities, 2) districts located in the south, and 3) districts with higher initial price levels. Indications of price bubbles are concentrated in the largest cities and in the purchasing market. Prices seem to be driven by the demand side: Increasing population density, higher shares of academically educated employees and increasing purchasing power explain our findings, while supply remained relatively constrained in the short term.
urn:nbn:de:gbv:3:2-870666
Keywords: R23; R31; 330; Germany; housing market; regional disparities; rental prices